Pengembangan Instrumen Penilaian Berbasis HOTS (Higher Order Thinking Skills) pada Kompetensi Dasar Menerapkan Sistem Penyimpanan Arsip SIstem Abjad, Kronologis, Geografis, Nomor, dan Subjek di Jurusan OTKP SMKN 1 Bojonegoro - Siti Fatimah; Triesninda Pahlevi (Universitas Negeri Surabaya, 2020)
The aim of this research are developing assessment instruments based on Higher Order Thinking Skills, knowing the appropriateness of Higher Order Thinking Skills based instruments and knowing students' higher order thinking skills. The test subject used is class X majoring in OTKP SMK 1 Bojonegoro which consisting of 108 students. The assessment instruments developed totaling 30 item multiple choice questions. The assessment instruments developed also went through the validation stage of material experts, evaluation experts, and linguists with 97% results with œvery strong criteria. Assessment instrument on the basic competencies to implement an archive, alphabetical, chronological, geographical, number, and subject storage system in the Department of OTKP SMK 1 Bojonegoro is very feasible to use. The trial results of the Higher Order Thinking Skills-based assessment instrument showed that the high-level thinking ability of students in class X of the Department of OTKP SMK 1 Bojonegoro was in the